Inverter Control of Scheme for IEEE1547-2018 Category3 in Fuel Cell Systems - Won, Su Yeon; Lee, Kyo Beum (Transactions of the Korean Institute of Electrical Engineers, 2022)
This paper presents an inverter control scheme for fuel cell systems in IEEE1547-2018 Category3. The current configuration of Grid-Connected fuel cell system has limitations Category3's LVRT (Low Voltage Ride Through) reponse, additional inverter are needed. The inverter operates in an abnormal state where the grid voltage is unstable, and normally supplies the voltage to BOP (Balance of Plant) of the fuel cell system. Simulated verification of the inverter control scheme was performed to change the voltage source to the BOP from grid to inverter during abnormal conditions.
Keywords: Balance of plant; Fuel cell system; Grid connected systems; IEEE1547; Ieee1547-2018 category3; Inverte; Inverter control; Inverter control schemes; Low voltage ride through; Lower Voltage Ride Through; Fuel cell; Grid-Connected system; IEEE1547-2018 Category3; inverter; LVRT (Low Voltage Ride Through)